Simultaneous capture of methyl orange and chromium(vi) from complex wastewater using polyethylenimine cation decorated magnetic carbon nanotubes as a recyclable adsorbent. Issue 9 (6th February 2019) - Chen, Bo; Yue, Wenli; Zhao, Huinan; Long, Fengxia; Cao, Yangrui; Pan, Xuejun
Abstract : An MWCNTs@Fe3 O4 /PEI composite was facilely fabricated as a robust adsorbent for simultaneously capturing methyl orange (MO) and Cr(vi ) from complex wastewater. Abstract : Most recently, the continuous deterioration of the aquatic environment triggered by both heavy metals and synthetic organic dyes has imparted serious threats to the ecosphere and drinking water safety. However, it is still extremely challenging to treat complex wastewater containing these two classes of pollutants via a one-step method owing to the significant differences in their physicochemical properties. In the current work, versatile magnetic MWCNTs decorated with PEI (denoted as MWCNTs@Fe3 O4 /PEI) was fabricated by a facile, rapid and reproducible strategy and applied to as a robust adsorbent for simultaneously removing methyl orange (MO) and Cr(vi ) from aqueous solutions. The physicochemical properties of the as-designed nanohybrid were investigated using various analytical techniques, i.e. XRD, FT-IR, SEM, TEM, VSM, zeta potential, etc. It was found that the surface charge properties of the MWCNTs as well as its dispersion in aqueous solution were greatly changed after the introduction of PEI molecules. The resulting nanohybrid exhibited attractive adsorption capabilities toward anionic MO and Cr(vi ). In the perspective of a mono-pollutant system, the time-dependent adsorption process matched well with a pseudo-second-order kinetics equation, the adsorption isotherm data at r.t. were well fitted by a Langmuir model with maximum monolayer uptake capacity of 1727.6 mg g −1 for MO and 98.8 mg g −1 for Cr(vi ), and the removal process of both pollutants was thermodynamically spontaneous and exothermic. In the MO-Cr(vi ) binary system, the uptake of Cr(vi ) by the as-prepared adsorbent was evidently enhanced by the presence of MO, while the coexisting Cr(vi ) exerted a small negative effect on the sorption of MO; which was attributed to the different adsorption mechanisms of both pollutants on the as-recommend adsorbent. The much better adsorbing performance of the resulting MWCNTs@Fe3 O4 /PEI for MO and Cr(vi ) than that of the pristine MWCNTs or the MWCNTs/Fe3 O4 composite was mainly ascribed to the high surface area of the MWCNTs, the high density of protonated N-rich groups of PEI as well as the excellent dispersion and solubility of the resulting nanocomposites. Moreover, the obtained nanohybrids can be easily recovered after being used by a permanent magnet and still retained high stability and excellent reusability after consecutive adsorption–desorption cycles, implying its great potential in practical applications. Therefore, the as-fabricated MWCNTs@Fe3 O4 /PEI composite could be recommended as a promising candidate adsorbent for the simultaneous capture of MO and Cr(vi ) from complex wastewater via multiple uptake mechanisms ( e.g. electrostatic attraction, π–π stacking and hydrogen bonding).